Hysteretic Implications for Graded Bed Load Sediment Transport in Symmetrical Hydrograph Flows - Wang, Le; Wang, Dayu; Cuthbertson, Alan; Zhong, Deyu; Pender, Gareth (Frontiers in Environmental Science, 2021)
Different parametric values associated with bed load sediment transport resulted from the same discharge on the rising and falling limbs in a flood hydrograph is usually defined as hysteresis, where the hysteresis of bed load transport rates is of considerable interest in the field of fluvial hydraulics. Here, a series of well-defined, symmetrical hydrographs are generated and flow over a non-uniform, mobile sediment bed in an attempt to fully examine the effect of hysteresis on bed load sediment transport in terms of threshold motion, bed load transport rate and bed load yields. All experiments are conducted in a titling flume without sediment supply specified from upstream inlet, thereby representing typical downstream reach of a dam that exclusively subject to net bed degradation during sediment transport in flood events. Our results show that the transport of defined fine, medium and coarse size classes within non-uniform sediment bed display clockwise, no/mixed and counter-clockwise hysteresis in general, clockwise hysteresis is commonly found for coarse size class mobilised by a hydrograph with long duration, by contrast, counter-clockwise hysteresis is usually observed for fine size class transported by a hydrograph in short duration. As a result, for bed load sediment transport in clockwise and counter-clockwise hysteresis, the reference stress used to describe sediment incipient motion in rising limb is lower and larger than in falling limb, respectively. Also, the reference stress for each size class varies between different hydrographs and basically controlled by the hydrograph’s flashiness and magnitude. Moreover, it is shown that the hysteresis effect, particularly those in clockwise and counter-clockwise behaviours must be accounted for when reproducing bed load transport rates using separate-limb based method. Finally, we investigated the relative amount of bed-load yields generated on rising and falling limb in all symmetrical hydrographs (i.e. bed-load yields ratio), which are primarily dependent on bed load transport hysteresis. Also, the relationship between the bed-load yields ratio and the ratio of reference stress for each size class sediment motion on both limbs is found to follow a power law.